Marketing, Mobile and future of Mobile Advertisement: Life Changing through Mobile - Bharti,; Kumar Garg, Sanjeev; Ghai, , Mandeep (International Journal of Psychosocial Rehabilitation, 2019)
In today’s competitive world when advertisement of any product decide it’s worth in the market and becoming the sole deciding factor or most influencing factor for consumers response to the product in the market while taking positive decision for the purchase. It becomes very important to find out the mode of advertisement where the customer is most available and the mode have more influence and appeal to the potential customers for positive decision making for purchase of the product in future. The present study is conducted to identify the level of mobile usage among the research population along with the future scope for the mobile advertisement in the region. The data is collected from 200 respondents with the help of structured questionnaire. The research supported the increasing use of mobile phones and time spent in the usage of various utility apps.